Copy of Trial of Dimethyl Sulfoxide on Systemic Tissue Damage Due to Kerosene Ingestion - Ozgen, Unsal (Annals of Medical Research, 2021)
None
Keywords: Kerosene ingestion, dimethyl sulfoxide , ischemic injury